The Effect Of Media Edutainment Education On Hand Washing Accurary In Grades 4 - 6 Students - Widhiyanto, Alwin; Yunita, Rizka; W.Q, Al Firdaus; Prasetyanto, Deni (Unit Penelitian dan Pengabdian Masyarakat STIKES Fatmawati Jakarta, 2023)
Children in school age are a period of acquiring the basics of knowledge. Various diseases that attack school-age children such as diarrhea, ARI, hepatitis, typhoid and bird flu, are generally related to daily behavior. To avoid sickness in youngsters, it is vital to carry out health education on hand washing. Health education in delivered through entertaining and engaging media prevent disease in children, it is necessary to carry out health education on hand washing. Health education is provided in the form of interesting and not boring media, like edutainment. The purpose of this study is to ascertain the impactelementary school pupils in grades 4 – 6. This research method uses pre-experimental design with One group pre post test design. This research was conducted at SDN Banjarsawah 1. The population was 30 respondents. The sampling technique used Total Sampling with 30 sampleof 30 respondents. The research instrument used an observation sheet. Analysis of the data used in this study using the Wilcoxon test. According to the findings, up to 25 respondents (83,3%) were determined to fall into the incorrect category of hand washing before receining edutainment media education. As many as 28 respondents (93,3%) were categorizet as practicing proper hand washing after receiving edutainment media education. The results of the analysis test showed that there was an effect of edutainment media education on the accuracy of hand washing with r-value = 0.000 <α = 0.05. It can be concluded that there is an effect of edutainment media education on the accuracy of hand washing in school children. Edutainment media can increase the accuracy of hand washing in children, so that further research can be carried out in other fields of study with the abilities possessed by various ages and characters.